(untitled) (Revista Justiça do Direito, 2019)
This study aims to analyze the issue of tax morality and ethical (or unethical) attitudes identifiable in the tax legal relationship, considering the performance of duties in its two faces, the public (tax authority) and the private (taxpayer). The work approaches the aspects of Tax Justice, Equity and Fair Tax, inspired by the teachings of Klaus Tipke, leading to the confirmation that a tax is sustainable not only when it respects the ability to contribute, but also when the society accepts it as legitimate and necessary, even in a context of high tax burden. Thus, for this to occur is fundamental that the State manifests an ethical posture in dealing with taxpayers and with the resource’s application, whether in order to legitimize this conduct or to inspire the taxpayers to adopt the same behavior, assuming that their misconduct (tax evasion) is a direct reflection of the State posture.